Expanding Patient Access and Engagement - Binik-Thomas, Justin; Fronczkowski, Barbara; Reinemeyer, Kathleen; Brown, Meggen (Journal of Applied Business and Economics, 2024)
Access to healthcare in the United States is drastically changing. The governmental response to the coronavirus greatly upended our ways of business. Rationing care damaged trust, instilled hesitancy for treatments and prevention, and functionally introduced medical deserts to poor and rural areas. The response by the practitioners was positive - empowering nurses, physician associates, and pharmacists to perform most patient-facing functions. This paper focuses on community care, primarily by nurse practitioners, where practitioners provide primary care and urgent care near or in existing pharmacies and supermarkets, building on relationships and convenience, thus maximizing patient access and mitigating risks.